2020
DOI: 10.1111/jch.13850
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to blood pressure control in China in a large opportunistic screening

Abstract: We investigated the prevalence, awareness, treatment, and control of hypertension in a large opportunistic screening study in China. Our study participants had to be ≥18 years of age and had ideally not taken blood pressure (BP) for ≥1 year. BP was measured three times consecutively in the sitting position with a 1-minute interval, using a validated electronic BP monitor or mercury sphygmomanometer. Trained volunteer investigators administered a questionnaire to collect information on medical history, lifestyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
9
1
Order By: Relevance
“…This study found the uncontrolled hypertension rate was 43.5% (in 2008), in the developed region in South China, in line with recent trends of the United States, where near half of patients achieved hypertension control across 20 American primary care centers, and the hypertension control increased from 27.3% in 1988–1994 to 50.1% in 2007–2008 in recent NHANES survey ( 10 12 ). Wang et al conducted MMM China project among 364,000 participants in 394 inside hospitals or community health centers and found that the awareness, treatment, and control rates of hypertension were 60.1, 42.5, and 25.4%, respectively, with the rate of uncontrolled hypertension (59.8%) moderately higher than our study ( 13 ). We only investigated the patients receiving antihypertensive treatment in the community, not patients in hospitals, which might present with higher control proportion.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…This study found the uncontrolled hypertension rate was 43.5% (in 2008), in the developed region in South China, in line with recent trends of the United States, where near half of patients achieved hypertension control across 20 American primary care centers, and the hypertension control increased from 27.3% in 1988–1994 to 50.1% in 2007–2008 in recent NHANES survey ( 10 12 ). Wang et al conducted MMM China project among 364,000 participants in 394 inside hospitals or community health centers and found that the awareness, treatment, and control rates of hypertension were 60.1, 42.5, and 25.4%, respectively, with the rate of uncontrolled hypertension (59.8%) moderately higher than our study ( 13 ). We only investigated the patients receiving antihypertensive treatment in the community, not patients in hospitals, which might present with higher control proportion.…”
Section: Discussioncontrasting
confidence: 74%
“…Our analysis also showed that the independent risk factors of uncontrolled hypertension are full-time work, self-financed medical care, non-marital status, poor cognition of hypertension diagnosis, poor cognition of hypertension treatment, poor drug compliance, and unwillingness for blood pressure measurement information reminder among patients in the community receiving antihypertensive treatment. MMM China project also showed that current smoking, no diabetes, no coronary heart disease, and older were independent risk factors of uncontrolled hypertension ( 13 ), while the above variables were not collected in our study. A recent review highlighted the important role of an education intervention on healthy behaviors and showed a moderate effect in the adherence to dietary recommendations and physical activity recommendations ( 7 ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This system was used to measure blood pressure in a large number of people who had not measured their blood pressure in the previous year in the framework of the international May Measurement Month (MMM) project. [14][15][16] The system is now used by hundreds of people every day in various public places, such as airports, shopping malls, and office buildings. It is hoped that with a sufficiently large number of blood pressure monitors deployed in the next few years, the system will substantially improve detection and management of hypertension in China.…”
Section: B Lood Pre Ssure Telemonitoringmentioning
confidence: 99%
“…However, as shown by the current initial endeavour, it will not be an easy task. First, the awareness of hypertension in China is still low, especially in the young [15]. That at least partially explains why in the present study the registered patients were relatively old.…”
Section: Discussionmentioning
confidence: 69%